Behavior of Post-Tensioned Concrete Girders Subject to Partially Strand Damage and Strengthened by NSM-CFRP Composites - Abbas Jalil; Alaa Hussein Al‐Zuhairi (Salehan Institute of Higher Education, 2022)
Studies on the flexural behavior of post-tensioned beams subjected to strand damage and strengthened with near-surface mounted (NSM) technique using carbon fiber-reinforced polymer (CFRP) are limited and fail to examine the effect of CFRP laminates on strand strain and strengthening efficiency systematically. Furthermore, a design approach for UPC structures in existing design guidelines for FRP strengthening techniques is lacking. Hence, the behavior of post-tensioned beams strengthened with NSM-CFRP laminates after partial strand damage is investigated in this study. The testing program consists of seven post-tensioned beams strengthened by NSM-CFRP laminates with three partial strand damage ratios (14.3% symmetrical damage, 14.3% asymmetric damage, and 28.6% symmetrical damage). The experimental results showed that the use of CFRP laminates significantly increases the flexural capacity by up to 17.4 to 20.4%, corresponding to a strand damage ratio of 14.3 and 28.6%, respectively, enhances the stiffness, and reduces strand strain by up to 15.8 to 22.2%. However, the flexural stiffness of strengthened beams during serviceability phases is critical as strand damage ratios increase. Additionally, semi-empirical equations were proposed to predict the actual strain of unbonded strands whilst considering the effects of CFRP laminates. The suggested equations provide accurate predictions with little variance. Doi: 10.28991/CEJ-2022-08-07-013 Full Text: PDF